Adverse effects of topical photodynamic therapy: a consensus review and approach to management. (1st April 2019) - Ibbotson, S.H.; Wong, T.H.; Morton, C.A.; Collier, N.J.; Haylett, A.; McKenna, K.E.; Mallipeddi, R.; Moseley, H.; Rhodes, L.E.; Seukeran, D.C.; Ward, K.A.; Mohd Mustapa, M.F.; et al.
Summary: Background: Topical photodynamic therapy (PDT) is widely used to treat superficial nonmelanoma skin cancer and dysplasia, and is generally well tolerated. However, as with all treatments, adverse effects may occur and awareness may facilitate approaches to prevention and management. Objectives: To review the available evidence relating to the adverse effects of topical PDT, to help inform recommendations in updated clinical guidelines produced by the British Association of Dermatologists and British Photodermatology Group, and the efficacy of preventative and therapeutic approaches. Methods: This review summarizes the published evidence related to the adverse effects of topical PDT and attempts to interpret this evidence in the context of patient risk and management. Results: Pain and discomfort during PDT are acute adverse effects, which can be minimized through the use of modified and low‐irradiance PDT regimens and do not therefore usually limit successful treatment delivery. Other adverse effects include the risk of contact allergy to photosensitizer prodrugs, although this is rare but should be kept in mind, particularly for patients who have received multiple PDT treatments to larger areas. There are no other significant documented longer‐term risks and, to date, no evidence of cumulative toxicity or photocarcinogenic risk. Conclusions: Topical PDT is usually well tolerated, reinforcing the utility of this important therapeutic option in dermatology practice. The main acute adverse effect of pain can typically be minimized through preventative approaches of modified PDT regimens. Other adverse effects are uncommon and generally do not limit treatment delivery.